Coincidence or Strategy? The Role of Accident in Creative Business Development - Judijanto, Loso; Syamsulbahri, Syamsulbahri (Westscience Press, 2025)
This study examines the role of accidental events in the creative business development of Indonesia, focusing on whether these incidents are merely coincidences or can be strategically leveraged. A quantitative approach was employed, with data collected from 150 respondents across various creative industries, including fashion, digital media, and design, using a 5-point Likert scale. Data were analyzed using SPSS version 25. The results reveal that entrepreneurs perceive accidental events as valuable opportunities for innovation, business growth, and gaining a competitive advantage. A significant positive correlation was found between the perception of accidents and innovation, as well as between strategic use of accidents and business growth and competitive advantage. The study highlights the importance of strategic adaptability in utilizing accidents as opportunities for fostering innovation and achieving business success. The findings provide insights into how accidental events can be harnessed to drive creative business development and strategic agility in a dynamic market environment.